Pengaruh Penggunaan Fitur TikTok Shop Terhadap Perilaku Konsumtif Fashion Mahasiswi Universitas Lambung Mangkurat - Fahri, Muhamad Agil; Zulaikha, Siti (Prodi Sosiologi FISIP ULM, 2025)
TikTok Shop has experienced rapid growth since 2021, with a projected 125 million users in Indonesia by 2024. Although it aims to facilitate shopping, its features and persuasive promotions have instead encouraged irrationally consumptive behavior. This study aims to investigate the impact of TikTok Shop usage on the consumption-related fashion behavior of female students at the Faculty of Social and Political Sciences (FISIP), Lambung Mangkurat University. A quantitative method with a correlational approach was employed, using a Likert scale to measure attitudes, perceptions, and consumptive behavior. The findings reveal that the majority of students exhibit a relatively high intensity of TikTok Shop usage, with a frequency of 3–5 times per week. Their usage is often driven by factors such as entertainment, product information, promotions, or discounts. Consumptive behaviors identified among respondents include purchasing decisions influenced by gifts, attractive packaging, and the desire to follow trends or maintain social prestige. TikTok Shop was found to have a significant impact on the consumptive fashion behavior of FISIP students, with 85 respondents displaying such tendencies. This behavior is reinforced by psychological and social motivations, such as the desire to maintain appearance and social status. It is therefore important for FISIP students to increase awareness of their consumption patterns and adopt a more mindful approach to shopping on e-commerce platforms. Future research is recommended to further explore psychological and social factors in greater depth from an academic perspective, while also offering practical recommendations for students in developing wiser consumption patterns.